Estimating coke fracture toughness using acoustic emissions and changes in coefficient of friction during scratch testing. (15th August 2018) - Lomas, Hannah; Roest, Richard; Wells, Adam; Wu, Hui; Jiang, Zhengyi; Sakurovs, Richard; Stuart, Russell; North, Lauren; Thorley, Tizshauna; Mahoney, Merrick R.
Highlights: Progressive loading scratch tests were conducted to understand microstructural and microtextural drivers for coke strength. An acoustic-based approach to assess energy release during coke fracture was developed. Characterisation of the acoustic emission peaks led to the identification of distinct signatures. The signatures classified acoustic emission maxima primarily by their relationship with the coefficient of friction. The signatures were linked to microtextural and microstructural attributes, and the mode of damage. Abstract: Acoustic emission profiles generated during scratch testing of a range of metallurgical coke samples were recorded and linked to the concurrent energy release, dispersal or absorption on coke fracture or damage. Three different signatures were identified, which were based on the simultaneous measurement of acoustic and total energy release profiles, and these signatures could be correlated with both the microstructure and microtexture of the coke being traversed at the time. The acoustic emission signature for fracture or damage to the coke reactive maceral derived constituents (RMDC) was correlated to the rank of the parent coal or coal blend, with the signature number generally increasing with increasing rank. Conversely, the signature numbers did not vary with parent coal rank for fracture or damage to the inertinite maceral derived constituents (IMDC), with the majority of IMDC fractures associated with a release of mechanical energy. The incidence of the signature associated with a release of mechanical energy (type 1) became increasingly dominant from RMDC to RMDC-IMDC interfaces to IMDC. Conversely, signature types associated with a dispersal (type 2) or absorption (type 3) of mechanical energy become increasingly dominant from IMDC to RMDC-IMDC interfaces to RMDC. The findings suggest acoustic emissions recorded during scratch testing and their subsequent characterisation can be used to indicate the fracture toughness of a given coke. This study contributes towards a broader program of research to improve understanding of the factors which influence the strength of coke and its microtextural constituents and interfaces, and how this relates to the properties of the parent coals.